2018
DOI: 10.1002/fuce.201700192
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Cell Electric Vehicle‐to‐Grid: Experimental Feasibility and Operational Performance as Balancing Power Plant

Abstract: The world's future energy supply will include intermittent renewable sources, such as solar and wind power. To guarantee reliability of supply, fast‐reacting, dispatchable and renewable back‐up power plants are required. One promising alternative is parked and grid‐connected hydrogen‐powered fuel cell electric vehicles (FCEVs) in “Vehicle‐to‐Grid“ systems. We modified a commercial FCEV and installed an external 9.5 kW three‐phase alternating current (AC) grid connection. Our experimental verification of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In the mentioned study, the cities in Spain and Germany are selected to analyze the total system cost of energy in terms of location selection, dimensioning, and component. [ 23 ] Oldenbroek, Hamoen [ 24 ] experimentally perform by using a commercial FCV connected to the grid, and system efficiency/hydrogen consumption issues are emphasized in the study. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the mentioned study, the cities in Spain and Germany are selected to analyze the total system cost of energy in terms of location selection, dimensioning, and component. [ 23 ] Oldenbroek, Hamoen [ 24 ] experimentally perform by using a commercial FCV connected to the grid, and system efficiency/hydrogen consumption issues are emphasized in the study. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…15 Because of large impact on acceleration and drive range on a single charge, battery is considered one of the most important components in HESS. 16 In some vehicle applications, 14,17 FCs are considered as an alternative energy converter to battery. If hydrogen is produced by a renewable energy source, the FC propulsion system produces no carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, little is known on the main technical difficulties with respect to fuel cell degradation and reliability of FCEVs operating in V2G. In our previous studies we have demonstrated the connection of a fuel cell electric car to the Dutch electrical grid providing V2G services [28]. As well the connection of a residential building operating in V2G mode was studied.…”
Section: Introductionmentioning
confidence: 99%